2015
DOI: 10.1016/s2095-3119(14)60924-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graded levels of fiber from alfalfa meal on apparent and standardized ileal digestibility of amino acids of growing pigs

Abstract: Two experiments were conducted to determine the effects of fiber level from alfalfa meal and sampling time on the apparent ileal digestibility (AID) and standardized ileal digestibility (SID) of amino acids (AAs) in growing pigs. A total of 24 ileal-cannulated pigs (Duroc×(Large White×Landrace), body weight (21.4±1.5) kg) were randomly allotted to 4 treatments. The pigs were provided a corn-soybean meal-control diet or a diet containing 5, 10 or 20% of alfalfa meal during two 10-d experimental periods. The AID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The result was caused by a higher fiber level in rice bran and alfalfa meal than in wheat middlings, because the concentration of dietary fiber has a negative effect on the digestibility of AA and nutrients [ 19 ]. Chen et al [ 20 ] reported that the corn-soybean meal diet containing 10% of alfalfa meal did not affect ileal AA digestion, but increasing the proportion of alfalfa meal from 12.3% to 21.4% in the control diet induced a linear reduction in AID of most AA. These results indicated that total ileal endogenous AA losses tended to increase with high concentration of fiber in diets fed to growing pigs [ 21 ], which is another reason for lower AID of AA in rice bran and alfalfa meal diets than in wheat middlings diet.…”
Section: Discussionmentioning
confidence: 99%
“…The result was caused by a higher fiber level in rice bran and alfalfa meal than in wheat middlings, because the concentration of dietary fiber has a negative effect on the digestibility of AA and nutrients [ 19 ]. Chen et al [ 20 ] reported that the corn-soybean meal diet containing 10% of alfalfa meal did not affect ileal AA digestion, but increasing the proportion of alfalfa meal from 12.3% to 21.4% in the control diet induced a linear reduction in AID of most AA. These results indicated that total ileal endogenous AA losses tended to increase with high concentration of fiber in diets fed to growing pigs [ 21 ], which is another reason for lower AID of AA in rice bran and alfalfa meal diets than in wheat middlings diet.…”
Section: Discussionmentioning
confidence: 99%